2016
DOI: 10.1152/ajplung.00158.2016
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A-mediated expression of epithelial IL-17C promotes inflammation during acutePseudomonas aeruginosapneumonia

Abstract: Lung epithelial cells are suggested to promote pathogen-induced pulmonary inflammation by the release of chemokines, resulting in enhanced recruitment of circulating leukocytes. Recent studies have shown that the interleukin-17C (IL-17C) regulates innate immune functions of epithelial cells in an autocrine manner. The aim of this study was to investigate the contribution of IL-17C to pulmonary inflammation in a mouse model of acute Pseudomonas aeruginosa pneumonia. Infection with P. aeruginosa resulted in an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 38 publications
(70 reference statements)
0
51
0
Order By: Relevance
“…Several groups confirmed this IL17C expression in keratinocytes (20)(21)(22)(23). Other epithelial cells producing the cytokine include colonic epithelial cells (9), resident kidney cells (24,25), and respiratory epithelial cells (26)(27)(28).…”
Section: Il-17c Is Expressed By Epithelial Cells and Not By Hematopoimentioning
confidence: 80%
See 1 more Smart Citation
“…Several groups confirmed this IL17C expression in keratinocytes (20)(21)(22)(23). Other epithelial cells producing the cytokine include colonic epithelial cells (9), resident kidney cells (24,25), and respiratory epithelial cells (26)(27)(28).…”
Section: Il-17c Is Expressed By Epithelial Cells and Not By Hematopoimentioning
confidence: 80%
“…The immune axis also plays a role in the defense against airway infections with Pseudomonas aeruginosa and Haemophilus influenza (26,27).…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…IL-17C is a member of the IL-17 cytokine family produced by epithelial cells, and is induced in response to bacterial (Ramirez-Carrozzi et al, 2011;Song et al, 2011;Pfeifer et al, 2013;Roth et al, 2014;Wolf et al, 2016;Steck et al, 2019;Jeon et al, 2020), viral (Ioannidis et al, 2012;Peng et al, 2017), or fungal infections (Conti et al, 2015;Huang et al, 2016). In the lung, several studies have shown that bacteria can induce IL-17C in cell culture systems and in animal models (Ramirez-Carrozzi et al, 2011;Pfeifer et al, 2013;Wolf et al, 2016). In the context of respiratory viral infections, one study observed that influenza virus, but not respiratory syncytial virus, induced IL-17C gene expression in human and murine bronchial epithelial cells at air-liquid interface (ALI) (Ioannidis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression studies have found IL-17RE to be primarily located on epithelial cells in mucosal tissues including the lung, trachea, mouth, stomach, and colon (Li et al, 2006;Ramirez-Carrozzi et al, 2011). Previous studies in murine and in vitro models have shown that IL-17C acts on the epithelium in an autocrine/paracrine manner to induce CXCL1 release and neutrophil recruitment (Wolf et al, 2016;Jamieson et al, 2019;Steck et al, 2019). But this has not yet been examined in highly differentiated HBE.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-a, IL-1b), which induce increased surface expression of TLRs and release of inflammatory mediators and AMPs. [29][30][31] The purpose of this study was to characterize the effect of hypoxia on the innate immune response of airway epithelial cells. We hypothesized that hypoxia suppresses the inflammatory response of airway epithelial cells during microbial infection and that HIF-1a mediates the suppressive effects of hypoxia.…”
Section: Introductionmentioning
confidence: 99%